Pre-transplant thymic function is associated with the risk of cytomegalovirus disease after solid organ transplantation. (May 2015) - Gracia-Ahufinger, I.; Ferrando-Martínez, S.; Montejo, M.; Muñoz-Villanueva, M.C.; Cantisán, S.; Rivero, A.; Solana, R.; Leal, M.; Torre-Cisneros, J.
Abstract: Cytomegalovirus (CMV) disease is an important complication in solid organ transplant recipients. Thymic function in adults is associated with specific T-cell immunity. Pre-transplant thymic function was analysed in 75 solid organ transplant patients by the use of nested PCR. The primary outcome was the incidence of CMV disease 12 months after transplantation. Using multivariable logistic regression, we studied whether pre-transplant thymic function is an independent risk factor for CMV disease after transplantation. Thymic function was related to the risk of CMV disease in CMV-seropositive recipients. In these recipients, pre-transplant thymic function of <9.5 (OR 11.27, 95% CI 1.11–114.43, p 0.040) and the use of thymoglobulin (OR 8.21, 95% CI 1.09–61.84, p 0.041) were independent risk factors for CMV disease at 12 months after transplantation. Patients with pre-transplant thymic function values of <9.5 had a higher subsequent incidence of CMV disease (24%) than patients with values of ≥9.5 (3%) (log-rank test: 5.727; p 0.017). The positive and negative predictive values of these pre-transplant thymic function cut-offs were 0.24 (95% CI 0.10–0.45) and 0.97 (95% CI 0.82–1.00), respectively. Pre-transplant thymic function in CMV-seropositive candidates could be useful in determining the risk of post-transplant CMV disease in solid organ transplant patients, selecting a group of low-risk candidates.